Passive monitoring techniques for elderly: a review on recent development and prospective - Arshad, Atika; Alam, A. H. M. Zahirul; Khan, Sheroz; Tasnim, Rumana (Newswood Limited, 2015)
Real time tracking and monitoring systems designed for observing the response of elderly population has proven its significance in recent years. The spectrum of sensing applications in tracking is on proliferation which is why it is important to review the progress of technological advancement and prospective of monitoring techniques. To implement a tracking system, a low cost, low power consumable, precise and wireless solution should be developed. The active tracking volume should be capable of facilitating a normal range of human motion. This paper highlights the review of various types of active and passive tracking system as well as the succeeding development leading to the design tasks. Moreover this paper briefs the operation and application of the ongoing monitoring approaches with their advantages and shortcomings.